Higher Education, Globalization and Eduscapes Towards a Critical Anthropology of a Global Knowledge Society - Forstorp, Per-Anders (Palgrave Studies in Global Higher Education,, 2018)
This book examines transnational scapes and flows of higher education: arguing that the educational and political vision of a national, regional and global knowledge society needs to be perspectivized beyond its ethnocentric conditions and meanings. Using eduscapes as its most important concept, this book explores the educational landscapes of individual as well as institutional actors; particularly the agential aspects of how global eduscapes are imagined, experienced, negotiated and constructed. In addition, the authors highlight the critical potential of anthropology, using this perspective as a resource for cultural critique where the Western experience and assumed 'ownership' of the global knowledge economy will be put into question. This comprehensive book will appeal to students and scholars of educational policy, the sociology of education and the globalization of education.